Geometric measure of mixing of quantum state - Laba, H.P.; Tkachuk, V.M. (Condensed Matter Physics, 2018)
We define the geometric measure of mixing of quantum state as a minimal Hilbert-Schmidt distance between
the mixed state and a set of pure states. An explicit expression for the geometric measure is obtained. It is
interesting that this expression corresponds to the squared Euclidian distance between the mixed state and
the pure one in space of eigenvalues of the density matrix. As an example, geometric measure of mixing for
spin-1/2 states is calculated. Ми означаємо геометричну мiру змiшаностi квантоваго стану як мiнiмальну вiдстань Гiльберта-Шмiдта
мiж змiшаним станом та набором чистих станiв. Отримано явний вираз для геометричної мiри змiшаностi. Цiкавим є те, що цей вираз вiдповiдає квадрату евклiдової вiдстанi мiж змiшаним та чистим станами
у просторi власних значень матрицi густини. Як приклад, обчислено геометричну мiру змiшаностi станiв
спiна 1/2.